2009
DOI: 10.3945/ajcn.2009.27747
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B-6 restriction tends to reduce the red blood cell glutathione synthesis rate without affecting red blood cell or plasma glutathione concentrations in healthy men and women

Abstract: Marginal vitamin B-6 deficiency tended to decrease mean RBC glutathione synthesis with no effect on RBC glutathione concentration, but the responses varied widely among individuals. Because the cysteine concentration in plasma and RBC did not change during vitamin B-6 restriction, we conclude that the effects of marginal vitamin B-6 deficiency on glutathione synthesis are not caused by altered precursor concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
(80 reference statements)
1
11
1
Order By: Relevance
“…The inverse relation between PLP and total glutathione found in this study is supported by previous studies showing slightly increased glutathione concentrations after vitamin B-6 restriction (16,42). In view of the fact that another vitamin B-6 restriction study showed no effect on plasma glutathione (43), the effects of vitamin B-6 on plasma glutathione appear to be weak and inconsistent. The lack of significant associations between PLP and creatine, creatinine, and dimethylglycine observed in this study was in contrast with the previously reported association of vitamin B-6 restriction with decreased plasma concentrations of these metabolites (20).…”
Section: Discussionsupporting
confidence: 66%
“…The inverse relation between PLP and total glutathione found in this study is supported by previous studies showing slightly increased glutathione concentrations after vitamin B-6 restriction (16,42). In view of the fact that another vitamin B-6 restriction study showed no effect on plasma glutathione (43), the effects of vitamin B-6 on plasma glutathione appear to be weak and inconsistent. The lack of significant associations between PLP and creatine, creatinine, and dimethylglycine observed in this study was in contrast with the previously reported association of vitamin B-6 restriction with decreased plasma concentrations of these metabolites (20).…”
Section: Discussionsupporting
confidence: 66%
“…As reported in a previous vitamin B-6 restriction protocol (26,27), mean fasting concentrations of plasma methionine, homocysteine, cysteine, serine, and glutathione exhibited no change associated with vitamin B-6 restriction in the present study. Similar to the pattern observed for cystathionine, the change in plasma glutathione concentrations in response to vitamin B-6 restriction correlated with the plasma glutathione concentration before vitamin B-6 restriction (r = 20.830; P , 0.001).…”
Section: Indicators Of Nutritional Status and Parameters Of 1-carbon contrasting
confidence: 63%
“…To minimize dietary variation immediately prior to the first infusion, participants consumed nutritionally adequate meals with a standardized composition for 2 d. On the day after the first infusion, participants began consuming a vitamin B-6restricted diet (,0.5 mg/d vitamin B-6) and continued this regimen for 28 consecutive days (25)(26)(27)(28). Mean total protein intake was 1 g · kg 21 · d 21 and mean methionine and cystine intakes were 21 and 17 mg · kg 21 · d 21 , respectively, during the vitamin B-6-restricted diet.…”
Section: Dietary Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythrocyte PLP might be an adequate alternative to plasma PLP and was shown to correlate with plasma PLP, plasma 4-pyridoxic acid, and dietary vitamin B-6 intake [68][69][70][71]. More data of reference ranges are required to validate erythrocyte PLP as an indicator of vitamin B-6 status.…”
Section: Vitamin B-6 Status Assessmentmentioning
confidence: 93%